HUBUNGAN KUALITAS SUSU DENGAN KERAGAMAN GENETIK DAN PREVALENSI MASTITIS SUBKLINIS DI DAERAH JALUR SUSU MALANG SAMPAI PASURUAN - Djoko Winarso (Jurnal Sain Veteriner, 2008)
The objectives of this study were to identify: (1) the differences of milk quality at the farmers' levels, postcollection, Village Cooperative Unit (VCU) and Milk Processing Industry (MPI), (2) the relation between milkprotein to genetic variety of kappa casein, (3) the relation between the milk bacteria and the subclinical mastitisprevalence. Completely Randomyzed Design followed by Least Significant difference test was used for analyzingthe milk quality. The alele and genotype frequency were analyzed using Hardy- Weiberg method, while theprevalence of subclinical mastitis was assessed using Chi-Square. The result of the research showed that thepercentage of chemical milk composition, based on the milk quality standard (Grade), from the level offarmerto post collection had the biggest decrease of milk quality, especially for fat content (59.32%), TSL (58.33%)and TPC (22.96%). Statistically especially there was no significance influence on the protein content of milk bythe frequency of alele A, alele B, genotype frequency AA and BB. Genotype frequency AB, showed significanceinfluence (P